SINGLE-STAGE AND DOUBLE-STAGE ACOUSTOOPTICAL TI-LINBO3 TE-TM CONVERTERS USED IN WAVELENGTH-SELECTIVE POLARIMETER AND POLARIZATION-INDEPENDENT DEPOLARIZER - REHAGE, M; Noé, Reinhold; HARIZI, C; RICKEN, R (FIBER OPTIC NETWORK COMPONENTS)

Weibliche" Ästhetik? Möglichkeiten und Grenzen einer Subversion von Codes - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft)

Guide to EXPRESS-P - Müller, Wolfgang; Felser, W.; Buijs, F. (Proceedings of the 4th EXPRESS User's Group)
Greenville, South Carolina

Complete Visual Specification and Animations of Protocols - Müller, Wolfgang; Lehrenfeld, Georg; Tahedl, C. (Proceedings of ASP-DAC'95/CHDL'95/VLSI'95 with EDA Technofair)
This article discusses the application of Pictorial Janus (PJ) for the rapid development and analysis of protocols by animation and complete visualization. In order to make PJ applicable in the context of hardware description we first extend PJ by timing facilities (Timed PJ) and introduce an approach for integrating VHDL models into this visual framework preserving the simulation semantics of VHDL. We finally give the example of the specification and animation of a non interlocked protocol.
Keywords: Animation; Protocols; Timing; Computer languages; Electronic mail; Context modeling; Visualization; Control systems; Flow graphs; Trademarks

An Editor for the Rapid Prototyping of EXPRESS-G Models - Zhao, R.; Müller, Wolfgang; Kaufmann, H. J.; Kern, Th.; Buijs, F. (Proceedings of the 5th EXPRESS User's Group)

The Process Modeling Language EXPRESS-P - Müller, Wolfgang; Felser, W.; Wiechers, N.

MULTISTAGE SPECTRAL POLARIMETER WITH GREATER-THAN-28DB STOPBAND ATTENUATION - Noé, Reinhold; REHAGE, M; TIAN, F (ELECTRONICS LETTERS)

Azimuthal Anchoring Energy in Photoinduced Anisotropic Films - Vorflusev, Valery P.; Kitzerow, Heinz-Siegfried; Chigrinov, Vladimir G. (Japanese Journal of Applied Physics)
Most electrooptic effects in liquid crystals require a uniform orientation of the director at the glass substrates. A new method to produce suitable alignment layers is based on the creation of anisotropic polymer films by photopolymerization with linearly polarized light. In the present paper we report on measurements of the anchoring strength of these photo-induced anisotropic films. Using a wedge-cell technique, we find an azimuthal anchoring energy of W ϕ ≈2.3·10 -6 J/m 2 .
Keywords: General Physics and Astronomy; General Engineering

Convolution algebras which are not necessarily positivity-preserving - Rösler, Margit (Applications of Hypergroups and Related Measure Algebras)

Trigonometric convolution structures on Z derived from Jacobi polynomials - Rösler, Margit (Journal of Computational and Applied Mathematics)
Keywords: Applied Mathematics; Computational Mathematics